2006
DOI: 10.1111/j.1399-6576.2006.01060.x
|View full text |Cite
|
Sign up to set email alerts
|

Regional differences in nitric oxide‐mediated vasorelaxation in porcine pulmonary arteries

Abstract: Our results show that endothelial-derived NO is an important factor influencing the differences between dorsal and ventral lung regions in vasorelaxing activity in porcine pulmonary arteries. This finding provides an explanation for the improved oxygenation when patients with severe acute lung insufficiency are turned prone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 38 publications
(58 reference statements)
1
8
2
Order By: Relevance
“…iNOS activity was generally lower than cNOS activity in both groups, which concurred with findings from previous studies in healthy and endotoxemic pigs [22,23]. Enzymes operate at an optimal intracellular pH, which can differ depending on cell type.…”
Section: Discussionsupporting
confidence: 80%
“…iNOS activity was generally lower than cNOS activity in both groups, which concurred with findings from previous studies in healthy and endotoxemic pigs [22,23]. Enzymes operate at an optimal intracellular pH, which can differ depending on cell type.…”
Section: Discussionsupporting
confidence: 80%
“…Furthermore, if NO was formed preferentially in dorsal lung as suggested by prior research (Pelletier et al, 1998 andRimeika et al, 2004), redistribution of Q to ventral lung should result with blockage of cNOS. However, we found a small but significant redistribution of Q from ventral to dorsal regions, Figure 10, contrary to what would be expected (Pelletier et al, 1998, Rimeika et al, 2004, Rimeika et al, 2006. There was no difference in total V/Q heterogeneity as a result of this small redistribution, which was also supported by a preserved PaO 2 and (A-a)O 2 difference.…”
Section: Minimal Change In V/q Distributions By L-namecontrasting
confidence: 54%
“…Beck and Rehder (Beck and Rehder, 1986) showed that vascular conductance was higher in dorsal lung in dogs in the supine, lateral and head-up positions, but the prone position was not examined. Evidence for uneven formation of NO in the lung was provided by in vitro studies showing greater eNOS activity in dorsal than in ventral lung regions in animals and humans, and similar regional differences in NO-mediated vasorelaxation in equine and porcine pulmonary arteries (Pelletier et al, 1998, Rimeika 2004et al, Rimeika et al, 2006. Rimeika et al (Rimeika et al, 2004) tried to confirm this by examining humans with SPECT in the prone and supine positions after inhibition of NO production.…”
Section: Endogenous No and V/q Matching Paper Iv: Inhibition Of Constmentioning
confidence: 96%
“…VB, 1 and 2). Alternatively, alteration of HPV by endogenous modulators such as NO could vary among regions (1633,1634).…”
Section: Edema Formationmentioning
confidence: 99%